ARE ISLAMIC BANKS STILL SOUND AMIDST PANDEMIC? - Clarashinta Canggih; Fira Nurafini; Sri Abidah Suryaningsih; Khusnul Fikriyah; Rachma Indrarini; Fitriah Dwi Susilowati (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The paper aims to check whether Islamic banks in Indonesia remain sound amid the Covid-19 Pandemic by comparing the soundness levels of Islamic commercial banks before and during the Covid-19 Pandemic. This research used a quantitative approach with the non-parametric Wilcoxon Signed-Rank Test to compare bank soundness before and during the Covid-19 Pandemic. The bank's resilience was measured using the Risk-Based Bank Rating (RBBR), e.g., Non-Performing Finance (NPF), Finance to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and Net Operating Margin (NOM). The study exempted aspects of Good Corporate Governance since it is qualitative. The study used quarterly data in 2018-2019 (before the pandemic) and 2020-2021 (during the pandemic). The results showed a significant difference between CAR before and during the Covid-19 Pandemic. Meanwhile, NPF, FDR, ROA, and NOM showed no significant differences before and during the Covid-19 Pandemic. Based on the results, it can be concluded that the Covid-19 Pandemic generally does not affect the Islamic banks' soundness level, except for capital. It showed that the Islamic Bank proved to be resilient against crises. The study adds literature on the resilience of Islamic banks, particularly during the Covid-19 Pandemic, and validates the RBBR measurement to analyze the bank's soundness. In addition, the results of this study are also expected to be a consideration for policymakers to design the right policies for optimizing Islamic banks to thrive and support post-pandemic recovery.